A clinical and histological comparison between acute cutaneous graft-versus-host disease and other maculopapular eruptions following hematopoietic stem cell transplantation: a retrospective cohort - Kumutnart Chanprapaph (2020)
© 2020 the International Society of Dermatology Background: Prompt management of acute graft-versus-host disease (GVHD) may prevent its morbidity and mortality. Maculopapular (MP) eruption is a presenting sign of acute GVHD, but differentiation from other causes of MP rash is challenging. Methods: A retrospective study was conducted among patients developing MP eruptions after allogeneic hematopoietic stem cell transplantation. We compared the clinical and histopathological differences between an acute cutaneous GVHD (group 1) and other MP eruptions (group 2). We also determined the clinical prognostic indicators linked to acute GVHD severity, morbidity, and mortality. Results: Of 95 patients identified, 75 met the classification criteria for acute GVHD, and 25 had other MP eruptions. Palm and/or sole involvement was more frequently found (51.4% vs. 12%, odds ratio [OR] [95% confidence interval] = 7 [2.1, 23.7], P < 0.01 and 41.4% vs. 0%, OR 37.2 [2.2, 635], P < 0.01, respectively) in group 1 than in group 2. Comparing the histological features between the two groups, necrotic keratinocytes in basal and spinous layers (92.9% vs. 22.2%, OR 27 [3.5, 594.7], P < 0.01) and (85.7% vs. 33.3%, OR 9.3 [1.4, 60.8], P = 0.02, respectively), diffuse basal vacuolization (42.9% vs. 0%, OR 14.5 [0.7, 298.2], P = 0.04), lymphocyte satellitosis (71.4% vs. 0%, OR 44.3 [2.1, 936.8], P < 0.01), and subepidermal clefts (42.9% vs. 0%, OR 14.5 [0.7, 298.2], P = 0.04) were significantly more apparent in group 1. Among extracutaneous presentations, diarrhea alone and/or accompanied by hyperbilirubinemia (47.1% vs. 16%, OR 4.3 [1.4, 13.1], P = 0.03 and 27.1% vs. 0%, OR 19.3 [1.1, 332.8], P < 0.01, respectively) and newly developed transaminitis (37.1% vs. 12%, OR 3.3 [1.1, 12.6], P = 0.02) suggested the diagnosis of acute GVHD. Mucosal involvement and/or blister formation correlated with severe acute GVHD (OR 26.6 [5.4, 130.4], P < 0.01). Skin and systemic GVHD severity correlated with time to rash resolution (P = 0.03 and P = 0.04, respectively), length of hospital stays (P < 0.01 and P < 0.01, respectively), and mortality (OR 4.87 [1.4, 17.4], P = 0.02 and OR 4.6 [1.3, 16.5], P = 0.02, respectively). Conclusions: Our findings may be beneficial tools for establishing the diagnosis of acute GVHD.